2021
DOI: 10.1142/s0217751x21501955
|View full text |Cite
|
Sign up to set email alerts
|

Bound state solutions of the Dirac equation for the generalized Cornell potential model

Abstract: In this study, the bound state solutions of the Dirac equation (DE) have been determined with the generalized Cornell potential model (GCPM) under the condition of spin symmetry. The GCPM includes the Cornell potential plus a combination of the harmonic and inversely quadratic potentials. In the framework of the Nikiforov–Uvarov (NU) method, the relativistic and nonrelativistic energy eigenvalues for the GCPM have been obtained. The energies spectra of the Kratzer potential (KP) and the modified Kratzer potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…One of the potential models that has significant contributions in the study of diverse systems in quantum chemistry and nuclear physics is the generalized Cornell potential (GCP) which is defined as [35–39]. Ur=ar2+brdr+fr2+V0, where a,b,d,f, and V0 are the potential parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the potential models that has significant contributions in the study of diverse systems in quantum chemistry and nuclear physics is the generalized Cornell potential (GCP) which is defined as [35–39]. Ur=ar2+brdr+fr2+V0, where a,b,d,f, and V0 are the potential parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Karayer [38] studied the solutions of the SE with the GCP in the presence of external magnetic and AB flux fields using the extended NU method. In Abu-Shady and Khokha [39], the solutions of the DE for the GCP were found using the NU method under the condition of spin symmetry. Moreover, the obtained results were applied to study some DMs and heavy mesons.…”
mentioning
confidence: 99%
“…In recent decades, the advent of new and powerful calculation software has allowed relativistic chemistry to develop and refine theoretical predictions on the physicochemical properties of matter. We are not only talking about the relativistic effects that have had experimental confirmation, well documented and discussed in the works of Pyykkö [3,4,17,18], but also those that are emerging from the study of innovative topological materials where theoretical chemistry has found a new fertile ground to test its potential [55][56][57][58][59]. In this article, we revisit the pillars on which the relativistic computational methods of chemistry are based, hidden in the lines of code that often are not clear to those who use such software.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The finding of the equation was based on the MSA in the integral equation theory of simple fluids, however, other approaches can be used for finding similar equations of the specific bond volume of Morse potential. The method which was employed for deriving the formula of the specific bond volume of Morse potential can be applied for other potentials, for instance: the dispersion potentials [38], the screening potential [30], and the two powers potential such as Lennard-Jones (6-12 type) potential and other types of the similar potentials [39][40][41][42][43][44][45], however, this study focused on the Morse potential.…”
Section: The Method: the Specific Bond Volume Of Morse Potentialmentioning
confidence: 99%